Cochlear nerve deficiency is an important cause of auditory neuropathy spectrum disorder at a population level in children. (July 2022) - Liddle, Karen; Fitzgibbons, E. Jane; Beswick, Rachael; Driscoll, Carlie
Abstract: Objectives: To determine the incidence, prevalence and describe risk factors and etiology for childhood Auditory Neuropathy Spectrum Disorder using population level data from a statewide universal newborn hearing program. Methods: A retrospective statewide universal newborn hearing screening database review and descriptive analysis from 2012 to 2019 of demographic, risk factors and hearing loss etiology for babies with sensorineural hearing loss and ANSD was completed. A 2 stage aABR protocol was used and ANSD was classified when click evoked ABR were absent or grossly abnormal but otoacoustic emissions and or cochlear microphonics were present. Medical evaluation and investigation by a pediatrician or otolaryngologist was performed and etiology was assigned using a coding scheme. Next generation genetic sequencing was not available. Results: From 2012 to 2019, 487 636 babies were screened for congenital hearing loss (99.1%) and 1150 were confirmed to have permanent SNHL, 80 of whom were diagnosed with ANSD (52 unilateral and 28 bilateral). The prevalence of ANSD was 7.0% and population prevalence was 0.16 per 1000 live births. The only demographic or risk factor significantly more likely to be associated with ANSD than SNHL was hyperbilirubinemia. The most common etiology for ANSD was hypoplasia or absence of the cochlear nerve with 37 cases (46.3%), and it was significantly more likely with unilateral than bilateral ANSD. Conclusion: At a population level, ANSD was more likely to be unilateral and the only perinatal risk factor significantly associated was hyperbilirubinemia. Cochlear nerve deficiency was the most common etiology. Given that this can occur in well babies, this provides further evidence for aABR as a preferred mode for newborn hearing screening.